Strategi Perencanaan Bisnis Teaching Factory Dalam Meningkatkan Kemampuan Entrepreneurship Siswa Melalui SWOT (Studi Kasus SMK Darut Taqwa Purwosari Kab. Pasuruan) - Sueb Sueb; Madziatul Churiyah (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to develop a Teaching Factory planning strategy to enhance the entrepreneurship skills of students at SMK Darut Taqwa. The SWOT analysis method was used in this study, with data collected through observation, interviews, and literature review. The SWOT analysis results indicate that Teaching Factory can strengthen the relationship with stakeholders and the community, and provide opportunities for students to develop entrepreneurship skills and insights. However, there are several limitations and weaknesses in implementing this strategy, such as limited resources and a lack of technology and digital platforms to support student entrepreneurship development. To address these issues, this study recommends several strategies, such as developing entrepreneurship training programs for students, identifying new resources to support student entrepreneurship development, and utilizing technology and digital platforms to support student entrepreneurship development. These strategies can help SMK students develop the necessary entrepreneurship skills and insights to compete with established businesses in the market. It is hoped that the results of this study can serve as a reference for educational institutions and the government in planning effective and sustainable entrepreneurship learning programs in the future.